PROSES PRODUKSI HASIL LAUT DALAM UPAYA MEMPEROLEH PRODUK UNGGULAN (Studi Kasus pada UD Yanis di Kelurahan Sukolilo Baru) - Yanda Bara Kusuma (Faculty of Social and Political Science, 2017)
The background of this research is city of Surabaya is famous with Kenjeran beach which has rich in marine products. Fishermen at Kenjeran beach get small and unique fish such as sea cucumber fish, lorjuk, eggplant, frozen fish, layur, shrimp, shark fin, and others. Fishermen on the Kenjeran beach exactly at New Sukolilo village has manage the results of his own sea. Most of the fisherman's produce is processed by the local Trading Company (Usaha Dagang) engaged in the processing of marine products. The research was conducted at UD Yanis, because UD Yanis is one of several UD of seafood processing in Sukolilo Village which has complete production permit. UD Yanis also process its own marine products, starting from the initial drying process until the finished product until packaging. The products that are the focus of researchers in the production process are crackers sea cucumber. This is due to crackers sea cucumber is a favorite product for consumers, regardless of the results of the sea season is not sea cucumbers. This study aims to answer the problem formulation that consists of (1) How is the production process conducted UD Yanis in processing sea products Keripuk Teripang in order to produce excellent products? (2) What are the constraints faced in the production process by UD Yanis in processing Sea Seaweed Crackers in order to produce excellent products? (3) How efficient production process as a solution for UD Yanis in managing sea cucumber crackers to produce excellent products? The type of research used in this study is explanatory research. Research approach in this research is qualitative approach. From the research results, it can be concluded that the attention in improving the processing of seafood can be done by producing efficiently and with good process. The simplicity of the production process resulted in reducing the amount of production that should be obtained. Increasing consumer demand, UD Yanis is required to increase its production output. From the constraints found, researchers develop the production process by updating existing tools with better quality. Some of the production tools include stainless steel pans, stoves made of steel and brass, and a large skillet made of steel plate. Because the growing process of production, will have an impact for the production of more sea cucumber crackers.